2007
DOI: 10.1017/s0265021506002304
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between lecture-based approach and case/problem-based learning discussion for teaching pre-anaesthetic assessment

Abstract: The effectiveness of lecture and case/problem-based learning discussion differed little in terms of improving participants' immediate knowledge of 'pre-anaesthetic assessment'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 11 publications
2
29
1
1
Order By: Relevance
“…According to the questionnaire results and the tutors, students showed more enthusiasm for PBL rather than LBL. It is reported that learning is most effective when students are actively involved in PBL28. Therefore, our results were consistent with previous conclusions, which may improve the application of lesion-based theory to practical knowledge as well as achieving specific goals.…”
Section: Discussionsupporting
confidence: 92%
“…According to the questionnaire results and the tutors, students showed more enthusiasm for PBL rather than LBL. It is reported that learning is most effective when students are actively involved in PBL28. Therefore, our results were consistent with previous conclusions, which may improve the application of lesion-based theory to practical knowledge as well as achieving specific goals.…”
Section: Discussionsupporting
confidence: 92%
“…We fully agree with Carrero and colleagues [1] that the impact of problem-based learning discussion on long-term acquisition of knowledge, skills and attitude should be defined. As described by these authors, the immediate retention of knowledge could be evaluated by a 'pre-tests and post-tests' objective tool.…”
supporting
confidence: 74%
“…In conclusion, now that problem-based learning is being introduced into anaesthesiology residents training programmes [1,3,4], our study showed that it may be applied for teaching not only clinical subjects, but also ethical reasoning. We fully agree with Carrero and colleagues [1] that the impact of problem-based learning discussion on long-term acquisition of knowledge, skills and attitude should be defined.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…The major advantages of PBL include deepening students' critical thinking, stimulating students' interests in their areas of study, motivating students' problem solving and therefore engagement [22] [23] [24] . However, the challenges do exist for the academically under-prepared student groups or when lack of appropriate tutor resources [25] [26] .…”
Section: Review Of Evidence-based Teaching Methodologiesmentioning
confidence: 99%